Rwanda : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criterion-Staff Report; Staff Supplement; Press Release. (IMF Staff Country Reports; Country Report ;, 2008)
The main risk to the program is that inflationary pressures would reemerge owing to improper management of the scaling up of aid and fiscal spending, or a protracted crisis in Kenya. The structural agenda focuses on maintaining the momentum in the previously initiated areas, particularly in the financial sector, tax administration, and public financial management. The authorities are launching a few large projects in energy, agriculture, and the information and telecommunication sectors aimed at easing binding infrastructure bottlenecks. Structural reforms advanced, albeit with some delays.